Evaluation of Hair Density and Hair Diameter in the Adult Thai Population Using Quantitative Trichoscopic Analysis. (10th February 2020) - Leerunyakul, Kanchana; Suchonwanit, Poonkiat
Abstract : The data of hair density and hair diameter in the Asian population, especially in Thais, are limited. We aimed to evaluate hair density and hair diameter of members of the Thai population at different scalp sites and to determine the effect of sex and aging as well as to compare the results with those in groups of other ethnicities. Healthy Thais whose hair examination findings were normal were evaluated. Two hundred and thirty-nine subjects participated in this study, of whom 79 were male and 160 were female. Hair density and hair diameter were analyzed at four different scalp sites using quantitative trichoscopic analysis. The highest hair density in Thais was observed in the vertex area. Hair densities at four different scalp sites were significantly different from one another; only hair density at the vertex site showed no significant difference from that in the occipital area. In contrast, hair diameter did not show any statistically significant differences for the different sites. We observed decreased mean hair density with increasing age and found statistically significant differences between participants in their 20s and those in their 60s, while hair diameter remained consistent. Comparing our results with a previous study in other ethnicities, the hair densities in Asians are generally lower. In conclusion, hair density in the Thai population varies at different scalp sites. Aging is a factor in declining hair density. Asians have a lower hair density compared to Caucasian and African populations.